INTERCONNECTION BETWEEN THE HEART AND LUNGS: PATHOPHYSIOLOGICAL PERSPECTIVES - Temirova Dilnoza Valiyevna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  The  heart  and  lungs  function  in  close  coordination  to  maintain oxygenation and circulation. Any dysfunction in one organ significantly impacts the other, leading to conditions such as pulmonary hypertension, cor pulmonale, and heart failure.  This  article  explores  the  physiological  and  pathophysiological  interactions between  the  heart  and  lungs,  highlighting  the  clinical  implications  of  their interdependence.